Crossing shades - Singh, Shareen (Rhodes University, Faculty of Humanities, Institute for the Study of English in Africa, 2020)
This collection of stories draw on culture, history, memory, musings and imagination. The stories are set primarily in South Africa but includes travels to other countries. I explore journeys to different worlds and minds. I challenge the reader to see how place and time influence our ways of seeing, living and evolving. I use different forms and tones that resonate with the subjective nature of each creative piece. My writing includes formal prose as well as works that experiment with fragments, vignettes and flash fiction.
Keywords: South African fiction (English) -- 21st century